2016
DOI: 10.1007/s12665-016-5639-9
|View full text |Cite
|
Sign up to set email alerts
|

Geo-parametric study of dredged marine clay with solidification for potential reuse as good engineering soil

Abstract: Dredging is an essential process in the development, expansion and maintenance of ports, jetties and various water bodies. The process of removing sediments to create or maintain certain water depths inevitably produces large amounts of dredge materials. These displaced materials are generally soils of fine-grained nature, i.e., clay and silt size particles with limited usability due to low strengths and high compressibility. Besides, exposure of the sediments to contamination via the waterways has made dispos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…It has been reported 19 that an ideal grain size distribution of the soil to achieve good quality bricks should have about 20–40% sand, 25–45% silt, and 20–35% clay-sized particles. Retrospective study In the same line, a previous study 20 has suggested that the suitable material for making clay bricks should contain about 30% of sand size particles as it reduces shrinkage that mostly occurs during the firing of soft clayey material.…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported 19 that an ideal grain size distribution of the soil to achieve good quality bricks should have about 20–40% sand, 25–45% silt, and 20–35% clay-sized particles. Retrospective study In the same line, a previous study 20 has suggested that the suitable material for making clay bricks should contain about 30% of sand size particles as it reduces shrinkage that mostly occurs during the firing of soft clayey material.…”
Section: Resultsmentioning
confidence: 99%
“…In Equation (1), when z = 0, the developed excess pore water pressure u at the ground surface upon the instantaneously applied surcharge (t = 0) is derived by:…”
Section: Drainage Boundary Conditionmentioning
confidence: 99%
“…However, the low permeability of dredged fills makes the developed excess pore water pressure more difficult to dissipate. Vertical drains can introduce radial drainage channels in the soil and decrease the seepage path, so they are often used to accelerate the consolidation of dredged fills [1][2][3]. Research on the consolidation theory of vertical drains has been carried out extensively.…”
Section: Introductionmentioning
confidence: 99%
“…The graph showing the change of specific gravity with respect to the OM has been given in Fig 5 . As a result of specific gravity experiments, it was determined that there is an inverse relationship between OM and specific gravity. This situation can be explained by the increase in the amount of carbon content and the weakening of the internal structure with the increase of OM [7], [27], [28], [29], [30].…”
Section: Index and Compressibility Properties Of Natural Dredged Soilmentioning
confidence: 99%